1987
DOI: 10.1002/1097-0142(19870301)59:5<1000::aid-cncr2820590525>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Controversy in the management of optic nerve glioma

Abstract: The records of 16 patients with optic nerve glioma treated between 1961 and 1984 were reviewed. All patients except two had extension of tumor beyond the chiasm to the hypothalamus, adjacent brain and/or along the posterior optic tract. Eleven of 16 cases were biopsy-proven, two patients had craniotomy and visual inspection but no biopsy was performed, and in two cases the biopsy was not diagnostic. Fourteen patients received radiation therapy, usually consisting of 50 Gy in 5 weeks (range 40-56 Gy), one patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Radiotherapy (RT) and radiosurgery might be more effective in posterior tumors than surgery alone in preventing relapse, but their morbidity should be taken into consideration. RT alone or after partial resection shows relapse-free rates of 56-90% (2) . Long-term prognosis, however, apparently does not change after any adjuvant treatment (3) .…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy (RT) and radiosurgery might be more effective in posterior tumors than surgery alone in preventing relapse, but their morbidity should be taken into consideration. RT alone or after partial resection shows relapse-free rates of 56-90% (2) . Long-term prognosis, however, apparently does not change after any adjuvant treatment (3) .…”
Section: Commentsmentioning
confidence: 99%
“…They occur most frequently in children and young adults, 75% of them in the first decade and 90% in the first two decades of life (1)(2)(3) . They may be confined to the optic disc and nerve (25%) or may involve the chiasma with or without the optic nerves in 20-40% of cases (1)(2) .…”
Section: Introductionmentioning
confidence: 99%
“…Failures occurred more rapidly after the second treatment. In the report of Weiss et al [76], one patient was reirradiated 8 years after primary treatment because of recurrent disease at a dose prescription of 30 Gy given in 3 weeks. He was reported to remain alive and well at 20 years with stable, although poor vision.…”
Section: Radiotherapy In Recurrent Diseasementioning
confidence: 99%
“…The risk of neurocognitive dysfunction and changes in behavior is an important issue in the management of low-grade glioma, as quality of life may be severely compromised [10,17,72]. Pollack et al [54] reported on complications and treatment-related sequelae presumably related to surgery followed by radiotherapy in glioma of the hemispheres.…”
Section: Neurocognitive Dysfunction/behavioral Changesmentioning
confidence: 99%
“…Danoff et al [17] reported on four of 15 living patients with mental retardation, two of whom were in semicomatose state after radiation therapy. Weiss et al [72] noted five of 16 patients with mental retardation after radiation, although one had meningitis as a possible causative factor. Deficits before radiotherapy are not unusual.…”
Section: Neurocognitive Dysfunction/behavioral Changesmentioning
confidence: 99%